Long-term association between water intake and kidney function in a population at high cardiovascular risk - Indira Paz-Graniel; Cristina Valle-Hita; Nancy Babio; Lluís Serra-Majem; Jesus Vioque; María Dolores Zomeño; Dolores Corella; Xavier Pintó; Naomi Cano-Ibáñez; Josep A. Tur; Esther Cuadrado-Soto; J.A. Martínez; et al. (Elsevier, 2024)
Objectives: The evidence on water intake in the prevention of kidney function decline is scarce at population level in well-being individuals at high cardiovascular risk. Therefore, we aimed to longitudinally evaluate the associations between total water intake and subtypes and kidney function, through estimated-Glomerular Filtration Rate (eGFR). Methods: Three-year prospective analysis conducted in 1986 older adults (aged 55-75 year) with overweight/obesity and metabolic syndrome from the PREDIMED-Plus study. Water intake was assessed using validated beverage and food frequency questionnaires. Serum creatinine-based eGFR (SCr-based eGFR; ml/min/1.73 m2) was estimated using the CKD-EPI equation at baseline, one-year and 3-years of follow-up. Mixed-effects linear regression models were fitted to evaluate the associations between baseline total water intake and subtypes, and SCr-based eGFR over 3-years of follow-up. Results: Participants in the highest baseline tertile of total water intake, plain water and water from all fluids showed a lower decrease in SCr-based eGFR after 3-years of follow-up, compared to those in the lowest tertile. Participants with the highest tap water consumption showed a lower SCr-based eGFR decline after 1-year and 3-years of follow-up, in comparerd to participants in the lowest intake category (T3 vs. T1: β: 1.4 ml/min/1.73 m2; 95%CI: 0.5-2.3, β: 1.0; 95%CI: 0.1-2.0, respectively). Conclusions: Plain water rather than other water sources, and especially tap water, was associated with lower kidney function decline assessed through eGFR over 3-years of follow-up, in older individuals at high cardiovascular risk. Trial registration: ISRCTN89898870. Retrospectively registered on 24 July 2014